(untitled) (Research, Society and Development, 2021)
Traffic accidents represent an important public health problem worldwide, due to the morbidity and mortality impact and quality of life of the victims, this article aimed to evaluate the predictive factors and the quality of life of victims of trauma due to traffic accidents. from an observational cross-sectional study. The sample was non-probabilistic for convenience, composed of 73 victims of trauma due to traffic accidents. Data collection occurred in two moments: (1) during hospitalization; and (2) after 90 days after the traumatic event. The instruments used to collect the data were the characterization of the sociodemographic profile and the traffic accident, and the World Health Organization Quality of Life (WHOQOL) Bref. The data were stored in spreadsheets of microsof excel 2013 and analyzed using the BioEstat 5.0 program. The predictive factors that revealed to have influence in the traffic accidents, were the masculine sex (OR: 39.6), alcohol use (OR: 31.7), absence of the individual protection equipment (OR: 3.00) and use motor vehicle on weekends (OR: 3.68). In assessing quality of life, the findings show that in trauma, the physical domain (35.1 ± 14.8) was the most altered when compared to the values before (80.5 ± 11.2) and after 90 days of trauma (54.0 ± 14.5). Traffic accidents were associated with men driving the vehicle, with alcohol consumption and not using personal protective equipment. In addition, the trauma is related to the negative impact on the victims’ quality of life.